Development and characterisation of bioactive films with antimicrobial properties for tissue engineering - Chee, Heng Li (2015)
In this study, PCL/MZ and PCL/GS films were produced aimed to be used as a drug delivery vehicle for local release of antibiotic drugs to control osteomyelitis and post operational infections. These films of varying concentrations (0%, 2.5%, 5%, 10%, and 20%) were fabricated via simple processing method involving cryomilling and heat pressing. Characterisation tests were subsequently carried out to determine the effects of MZ and GS on the physical properties of PCL, and to evaluate the release characteristics, microbial inhibition ability and cell proliferation and metabolism effects of PCL/MZ and PCL/GS films. The results suggested that MZ and GS particles were well dispersed and homogeneously distributed across the film surface and that increasing the drug concentration resulted in an overall reduction in tensile strength of the film. Release characteristics determined through the immersion of PCL/MZ films in DI water and PCL/GS films in PBS displayed an initial burst release and subsequent prolonged release over a period of 8 and 3 days respectively. Bacterial inhibition studies conducted with Clostridium Sporogenes, Pseudomonas Aeruginosa and Staphylococcus Aureus strains proposed that the antibiotics did not lose its inhibiting function after fabrication and displayed an increasing ZOI with increasing drug concentration. Finally, results from live/dead and cell metabolism assays suggested encouraging mesenchymal stem cells (MSCs) adhesion and proliferative capacity across all concentrations by day 7 even if it was comparatively lower than PCL. Taken together, these are encouraging results for the further development of PCL/MZ and PCL/GS films for drug delivery applications.